2017
DOI: 10.1021/acsomega.7b00321
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into and Characterization of the Aqueous Metal-Enol(ate) Complexes of (Acetonedicarboxylato)copper

Abstract: Nearly 50 years have passed since the classic studies by Larson and Lister [ Larson D. W. Lister M. W. Larson D. W. Lister M. W. Can. J. Chem. 1968 , 46 823 and Hay and Leong [ Hay R. W. Leong K. N. Hay R. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Oxaloacetic acid(OAA) is a β-keto acid, it plays a central role in several metabolic pathways such as the tricarboxylic acid cycle, gluconeogenesis, fatty acid biosynthesis, amino acid degradation, and amino acid biosynthesis [7][8][9][10][11]. The β-Decarboxylation of oxaloacetate(OA) can be catalyzed by a number of agents including amines [12][13][14][15], enzymes [16][17][18][19][20][21][22], et al Since Krampitz & Werkman reported that Mg( Ⅱ ) can accelerate the decomposition of oxaloacetate [23], many metal ions catalyzed decarboxylation of oxaloacetic acid have been studied [24][25][26][27][28][29][30][31][32][33][34][35][36], a number of multivalent cations (Cu(Ⅱ), Fe(Ⅱ), Co(Ⅱ), Ni(Ⅱ), Zn(Ⅱ), etc.) are shown have good catalytic activity in the ketone decarboxylation.…”
Section: Introductionmentioning
confidence: 99%
“…Oxaloacetic acid(OAA) is a β-keto acid, it plays a central role in several metabolic pathways such as the tricarboxylic acid cycle, gluconeogenesis, fatty acid biosynthesis, amino acid degradation, and amino acid biosynthesis [7][8][9][10][11]. The β-Decarboxylation of oxaloacetate(OA) can be catalyzed by a number of agents including amines [12][13][14][15], enzymes [16][17][18][19][20][21][22], et al Since Krampitz & Werkman reported that Mg( Ⅱ ) can accelerate the decomposition of oxaloacetate [23], many metal ions catalyzed decarboxylation of oxaloacetic acid have been studied [24][25][26][27][28][29][30][31][32][33][34][35][36], a number of multivalent cations (Cu(Ⅱ), Fe(Ⅱ), Co(Ⅱ), Ni(Ⅱ), Zn(Ⅱ), etc.) are shown have good catalytic activity in the ketone decarboxylation.…”
Section: Introductionmentioning
confidence: 99%